2021
DOI: 10.1038/s41598-021-97159-w
|View full text |Cite
|
Sign up to set email alerts
|

Smart-cut-like laser slicing of GaN substrate using its own nitrogen

Abstract: We have investigated the possibility of applying lasers to slice GaN substrates. Using a sub-nanosecond laser with a wavelength of 532 nm, we succeeded in slicing GaN substrates. In the laser slicing method used in this study, there was almost no kerf loss, and the thickness of the layer damaged by laser slicing was about 40 µm. We demonstrated that a standard high quality homoepitaxial layer can be grown on the sliced surface after removing the damaged layer by polishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…[14][15][16] The slicing of semiconductor wafers can be realized by exfoliating the damage layer from the perfect single-crystal region via mechanical stress, swelling stress, or thermal stress. [9,17,18] By replacing wire sawing with ultrafast laser slicing, the material loss and slicing duration per wafer are significantly reduced. [9,19] Moreover, the machining of ultrafast laser-sliced 4H-SiC includes only fine lapping and CMP, which further reduces the processing loss and improves the processing efficiency of 4H-SiC wafers.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The slicing of semiconductor wafers can be realized by exfoliating the damage layer from the perfect single-crystal region via mechanical stress, swelling stress, or thermal stress. [9,17,18] By replacing wire sawing with ultrafast laser slicing, the material loss and slicing duration per wafer are significantly reduced. [9,19] Moreover, the machining of ultrafast laser-sliced 4H-SiC includes only fine lapping and CMP, which further reduces the processing loss and improves the processing efficiency of 4H-SiC wafers.…”
Section: Introductionmentioning
confidence: 99%
“…[1] GaN was one of the materials affected by the shortage of semiconductors, which is important for the technological industry due to their optical and electrical properties, with applications in GaN-based power devices, full-color displays, Schottky barrier diodes, light-emitting diodes, highfrequency devices, laser diodes, highelectron-mobility transistors, piezoelectric microelectromechanical systems devices, and solar cells. [2][3][4][5][6][7][8] However, the global semiconductors shortage begins to decrease, and new applications of GaN for nanotechnology and microtechnology are investigated, owing to its wide bandgap of 3.4 eV (wurtzite structure) and 3.2 eV (zincblende structure). GaN nanostructures, such as nanorods, nanowires, nanotubes, GaN microneedle crystals are grown via GaAs substrates decomposition, using ultrahigh-pure anhydrous ammonia as nitrogen precursor at 900 °C for 4 min.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, a recycling process for GaN substrates using a laser slicing technique has been developed. [35][36][37][38] Figure 1 shows an overview of the GaN substrate recycling process. The thicknesses described in the figure represent the design values of the experiment in this study.…”
mentioning
confidence: 99%
“…Tanaka et al has reported that GaN high electron mobility transistors exhibit similar electrical properties before and after laser slicing to a thickness of 50 μm 35) and that a 8-μmthick epitaxial layer could be successfully grown on the GaN substrate after laser slicing. 36) However, the electrical properties of the devices on a recycled wafer, which are essential to demonstrate the recyclability of a GaN substrate, have yet to be investigated.…”
mentioning
confidence: 99%